2000
DOI: 10.1002/(sici)1096-9071(200004)60:4<432::aid-jmv11>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the duration and magnitude of viraemia in children hospitalised during the 1996-1997 dengue-2 outbreak in French Polynesia

Abstract: The magnitude and duration of viraemia in children admitted to the hospital with dengue was studied during a dengue 2 outbreak in French Polynesia in 1996-1997. Forty-nine patients from whom at least 3 plasma samples were available were included in the study. Based on analysis of IgG-ELISA and haemagglutination inhibition assay, 21 of these were primary and 28 were secondary infections. According to World Health Organization criteria, 42 were dengue fever and 7 were dengue haemorrhagic fever. Virus was detecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
90
1
6

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 33 publications
8
90
1
6
Order By: Relevance
“…Previously, we found variation from subject to subject in DV-specific T cell responses after primary infection (41), but those subjects were not subsequently challenged with DV and there is no information about subsequent natural exposures to DV in that group. Recently, studies from our group and others have shown that plasma titers of infectious DV or DV RNA are higher in subjects with DHF than in those with DF (45)(46)(47). We have also found that immune activation, as measured by plasma levels of soluble TNF receptors, soluble IL-2 receptors, IFN-␥, and IL-10, correlated with peak plasma DV RNA levels and that the peak plasma DV RNA level was the only one of these factors independently associated with the severity of plasma leakage by multiple regression analysis (47).…”
Section: Discussionmentioning
confidence: 91%
“…Previously, we found variation from subject to subject in DV-specific T cell responses after primary infection (41), but those subjects were not subsequently challenged with DV and there is no information about subsequent natural exposures to DV in that group. Recently, studies from our group and others have shown that plasma titers of infectious DV or DV RNA are higher in subjects with DHF than in those with DF (45)(46)(47). We have also found that immune activation, as measured by plasma levels of soluble TNF receptors, soluble IL-2 receptors, IFN-␥, and IL-10, correlated with peak plasma DV RNA levels and that the peak plasma DV RNA level was the only one of these factors independently associated with the severity of plasma leakage by multiple regression analysis (47).…”
Section: Discussionmentioning
confidence: 91%
“…that 3.9% of patients were primary infections and the other 96.1% were re-infection cases [14,15]. These reports suggested that dengue infections in primary infections produced slight symptoms or were asymptomatic, while that in re-infection generated more acute symptoms [3,33]. It was considered that ADE could influence the increased risks of progress to a symptomatic state and increased transmission probability for re-infection.…”
Section: Figure 9 Figure 10mentioning
confidence: 99%
“…It has long been assumed, but not empirically verified, that people with inapparent infections fail to infect mosquitoes because they do not reach sufficiently high viremia levels (5). This assumption is based on the observation that disease severity is positively correlated with the magnitude of DENV viremia (10,11,14). To our knowledge, the only study that quantified viral RNA levels in a limited number of asymptomatic DENV infections in humans did not detect a significantly lower viremia (15), but infectiousness to mosquitoes was not evaluated.…”
mentioning
confidence: 99%
“…aegypti fed on viremic people were able to transmit virus to another person after at least 11 d of extrinsic incubation (8). Results from later studies indicated that, for naturally infected people with clinically apparent dengue, the duration of detectable viremia was on average 4-5 d after the onset of symptoms, but could range from 2 to 12 d (9,10). Investigators in Vietnam fed Ae.…”
mentioning
confidence: 99%